Time-Aware Multi-Agent Symbiosis - Maniadakis, Michail; Hourdakis, Emmanouil; Sigalas, Markos; Piperakis, Stylianos; Koskinopoulou, Maria; Trahanias, Panos (Frontiers in Robotics and AI, 2020)
Contemporary research in human-machine symbiosis has mainly concentrated on enhancing relevant sensory, perceptual and motor capacities, assuming short-term and nearly momentary interaction sessions. Still, human-machine confluence encompasses an inherent temporal dimension that is typically overlooked. The present work shifts the focus on the temporal and long-lasting aspects of symbiotic human-robot interaction (sHRI). We explore the integration of three time-aware modules, each one focusing on a diverse part of the sHRI timeline. Specifically, the Episodic Memory considers past experiences, the Generative Time Models estimate the progress of ongoing activities, and the Daisy Planner devices plans for the timely accomplishment of goals. The integrated system is employed to coordinate the activities of a multi-agent team. Accordingly, the proposed system (i) builds upon past experiences to predict human preferences, (ii) monitors human activity to reckon task completion time and make estimates on human performance and emotional state, and (iii) develops flexible multi-agent activity plans that are dynamically adapted to the predicted temporal expectations of the human. The system is deployed and extensively assessed in real-world and simulated environments. The obtained results suggest that building upon the unfolding and the temporal properties of team tasks can significantly enhance the fluency of sHRI.